Solving a Challenge in the Tequila Industry: A New Continuous Rectification Process for Reducing Higher Alcohols and Obtaining Products Within the Official Tequila Standard - Héctor Flores-Martínez; Isaac Guadalupe Tejeda-Arandas; Mirna Estarrón-Espinosa; José Daniel Padilla-de la Rosa (ChemEngineering)
This work is the first to study the effect of residence time on the volatile composition of distilled fractions of ordinario using a horizontal continuous distiller of our own manufacture. The ordinario used in this research had a high amount of higher alcohols, so its adequate distillation is complicated. The fractions rectified by continuous distillation were compared with those obtained by batch distillation. Five distilled fractions were collected, and their combined volume was subjected to gas chromatography (GC) analysis to determine the principal volatile compounds (furfural, aldehyde, higher alcohols, methanol, and ester contents). A variance analysis of each group of volatile compounds was conducted to evaluate the effect of residence time (2 and 4 h) in continuous distillation compared to batch distillation (4 h). Continuous rectification allowed for obtaining a distillate within the permissible limits specified by the Official Mexican Standard (NOM-006-SCFI-2012). For the continuous 2 h, continuous 4 h, and batch 4 h processes, the higher alcohols, esters, and aldehydes showed a decreasing pattern, while methanol and furfural showed an increasing pattern in relation to the fraction number. An analysis of variance showed no statistically significant differences in terms of the regulated volatile composition (higher alcohols, esters, methanol, and furfural) according to process type (continuous 2 h, continuous 4 h, and batch 4 h), except for aldehydes, which presented differences. This new continuous rectification process increases productivity while reducing the processing time by 50%, keeping the composition and volume of the heart fraction.